Identifying the Hydrochemical Characteristics and Genetic Mechanism of Medium-Low Temperature Fluoride-Enriched Geothermal Groundwater in the Hongjiang—Qianshan Fault of Jiangxi Province - Shouchuan ZHANG; Kai LIU; Luyao WANG; Wei ZHU; Yuefei DENG; Chenghua YU (Yankuang ceshi)
The Hongjiang—Qianshan fault has abundant medium-low temperature geothermal resources. However, the excessive fluorine concentration in geothermal groundwater restricts the development and utilization of geothermal resources. 20 samples were collected in this region for identifying the genetic mechanism of medium-low temperature of fluoride-enriched geothermal resources. The hydrochemical results indicate that the hydrochemical characteristic of high fluoride geothermal groundwater is HCO3-Na. The groundwater environment is alkaline and weakly alkaline. The fluoride concentration in geothermal groundwater is 2−12 times greater than the upper limited value, while those in the surface water and shallow groundwater are within the permittable threshold range. The isotopic results reveal that the recharge elevations and circulation depth are 797−2186m and 893−1893m, respectively. Quartz provides the most reliable estimations of reservoir temperatures, ranging from 79.4℃ to 113.1℃. The fluoride in geothermal groundwater originates from the rock weathering and mineral dissolution. Cation exchange and alkaline condition are the main influence factors for fluorine enrichment. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.yk202403030028.